Neuropsychological deficits in Posterior Cortical Atrophy and typical Alzheimer's disease: A meta-analytic review. (October 2021) - North, Courtney; Desai, Roopal; Saunders, Rob; Suárez-González, Aida; Bamiou, Doris; Costafreda, Sergi G.; de Haan, Gera; Halls, Georgia; Heutink, Joost; O'Nions, Elizabeth; Utoomprurkporn, Nattawan; John, Amber; et al.
Abstract: Aims: To identify cognitive tests that best differentiate between Posterior Cortical Atrophy (PCA) and typical Alzheimer's Disease (tAD), as well as PCA and healthy control (HC) participants. Method: Medline, PsycInfo and Web of Science were systematically searched using terms related to PCA, tAD, and cognitive testing. Seventeen studies were identified, including 441 PCA, 391 tAD, and 284 HC participants. Standardised effect sizes of mean scores were calculated to measure performance differences on cognitive tests for PCA versus tAD and PCA versus HC groups. Meta-analyses used a random effects model. Results: The most discriminating cognitive tests for PCA and tAD presentations were measures of visuospatial function and verbal memory. Large, significant effect sizes were produced for all measures of visuospatial function, most notably for Rey–Osterrieth Copy (Hedges' g  = −2.79), VOSP Fragmented letters (Hedges' g  = −1.73), VOSP Dot Counting (Hedges' g  = −1.74), and VOSP Cube Analysis (Hedges' g  = −1.98). For measures of verbal memory, the RAVLT delay and Digit Span Backwards produced significant medium effects (Hedges' g  = .62 and −.56, respectively). Conclusion: Establishing a common framework for testing individuals with PCA has important implications for diagnosis and treatment, and forms a practical objective for future research. Findings from this meta-analysis suggest that measures of visuospatial function and verbal memory would form an important part of this framework.